MODEL ADOPSI PRODUK BANK SYARI’AH DI KUDUS: PENGEMBANGAN THEORY OF REASONED ACTION DAN SYARIAH COMPLIANCE - Anita Rahmawaty (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2014)
This study aims to analyze adoption model of Islamic bank products based onTheory of Reasoned Action (TRA) on the societies in Kudus. This study is a typeof survey research by using a quantitative approach. The research data areobtained from 140 respondents by using convenience sampling technique. Forresearch model testing technique, it used the statistical test Discriminant Analysis.The findings of this study is shown that the value of 0.753 CR2. If this value issquared (0,753)2 = 0,567, meaning that all discriminant variables (subjectivenorm,  attitude  towards use, syariah  compliance  and  trust)  can explain thedifferences in  people’s behavior  towards Islamic bank products  between thecustomers of Islamic bank (adopter) and non-customers (non-adopter) by 56,7%.While the adoption rate of product acceptance  in  the Islamic bank can be predictedwith four predictor variables with the classification level of 95.7% with two levelsof adoption of Islamic bank products (adopters and non-adopters).